2020
DOI: 10.1155/2020/9792170
|View full text |Cite
|
Sign up to set email alerts
|

Undesirable Postoperative Anesthesia Outcomes at Two National Referral Hospitals: A Cross-Sectional Study in Eritrea

Abstract: Background. Postoperative undesirable anesthesia outcomes are common among patients undergoing surgery. They may affect body systems and lead into more serious postoperative problems. This research is conducted in the Eritrean National Referral Hospitals with the aim of assessing the prevalence of undesirable anesthesia outcomes during the postoperative period. Method. A cross-sectional study design was applied on 470 patients who underwent different types of surgeries within a three-month period. Patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 34 publications
2
11
5
Order By: Relevance
“…This study aimed to investigate prevalence of postoperative thirst and the contributing factors associated with it. Our study found that thirst occurs in more than half of post-surgical patients (59.4%)).The result of this study is considerably high as compared to a studies done in Eritrea with prevalence of postoperative thirst (27.7%) [ 15 ] and Kenya (43.1%) [ 16 ]. This discrepancy might be underestimation of the problem and the quality of PACU differ from country to country.…”
Section: Discussioncontrasting
confidence: 38%
“…This study aimed to investigate prevalence of postoperative thirst and the contributing factors associated with it. Our study found that thirst occurs in more than half of post-surgical patients (59.4%)).The result of this study is considerably high as compared to a studies done in Eritrea with prevalence of postoperative thirst (27.7%) [ 15 ] and Kenya (43.1%) [ 16 ]. This discrepancy might be underestimation of the problem and the quality of PACU differ from country to country.…”
Section: Discussioncontrasting
confidence: 38%
“…POP was previously stated the most undesirable outcome. 5 In reflection to that, in this current study, the prevalence of POP in the immediate post-surgery in the SBM group was found to be 88.1%, but in the EM, group was 98.3%. The reason for the decrease of the POP prevalence in the SBM group could be due to the effect of pre-emptive analgesia which was given 1 hour before surgery.…”
Section: Discussionsupporting
confidence: 69%
“…4 The goals of effective and appropriate pain management is to improve quality of life for the patient, facilitate rapid recovery and return to full function, reduce morbidity and allow early discharge from hospital. 5 The WHO analgesic ladder outlines simple techniques using minimal resources to combat pain. 6 Non pharmacological methods also play an important role as a sole or in combination for reliving postoperative pain.…”
Section: Introductionmentioning
confidence: 99%
“…Unfavorable anesthetic outcomes are adverse events that can affect all of the patient’s body systems. 1 , 2 …”
Section: Introductionmentioning
confidence: 99%
“…These may arise from the squeal of operations, anesthetic and analgesic agents, worsening co-morbidities. 1 …”
Section: Introductionmentioning
confidence: 99%